Q2q: An R Package for Interpolating Age-Specific Mortality Rates at All Ages - Farid Flici (Journal of Open Research Software)
Q2q is a R package that simplifies the interpolation of age-specific mortality rates across all ages, starting from abridged life-tables. Due to differences in the age-patterns of mortality rates at juvenile and adult ages, it is challenging to identify a unique method to interpolate mortality rates at both age categories with sufficient quality. Typically, the six-term interpolation formula of Lagrange and the Karup king formula are used for younger and older ages, respectively. The Q2q package combines the two methods, with a junction point defined as the point where the two obtained mortality curves are the closest possible. The package is publicly accessible on CRAN and Github, and may be used for both annual and multi-annual data.